2021
DOI: 10.3389/fpubh.2021.645091
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dental Caries and Associated Factors in East Africa, 2000–2020: Systematic Review and Meta-Analysis

Abstract: Background: Dental caries affects mastication, growth and development, and school attendance and has a long-term psychological effect on affected individuals. In developing countries, the prevalence of dental caries is increasing due to the growing consumption of sugary foods, poor tooth brushing habits, and a low level of awareness about dental caries. Even if there was a high prevalence of dental caries in sub-Saharan Africa, there is a paucity of data on the prevalence of dental caries in East Africa. Hence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
34
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 74 publications
(53 reference statements)
9
34
2
1
Order By: Relevance
“…Gender also showed significant association, where females were more prone to caries in the current study than males, which is in a line with several other studies [52,53]. Girls usually exhibit earlier eruption of teeth than boys which subject them to higher caries incidence [54]. Additionally, dental fear was reported to be higher among girls than boys, which might hinder girls from going to dental visits and performing needed dental treatment [55,56].…”
Section: Discussionsupporting
confidence: 90%
“…Gender also showed significant association, where females were more prone to caries in the current study than males, which is in a line with several other studies [52,53]. Girls usually exhibit earlier eruption of teeth than boys which subject them to higher caries incidence [54]. Additionally, dental fear was reported to be higher among girls than boys, which might hinder girls from going to dental visits and performing needed dental treatment [55,56].…”
Section: Discussionsupporting
confidence: 90%
“…This study revealed a high prevalence of dental caries, 64.6%, which is comparable with a cross-sectional study conducted in Turkey (62%) that involved large sample size [ 11 ]; however, it is higher than school-based cross-sectional studies conducted in Kenya 37.5% [ 12 ], Bahirdar, Ethiopia (21.8%) [ 13 ], North West, Ethiopia (36%) [ 14 ], and a hospital-based cross-sectional-study conducted in Gondar, Ethiopia (23.64%) [ 15 ]. A systematic review and meta-analysis conducted in East Africa (45.7%) [ 16 ] and Ethiopia (40.98%) [ 17 ] and a school-based cross-sectional study conducted in Shawa, Ethiopia [ 18 ] also revealed a low prevalence of dental caries as compared to the current study.…”
Section: Discussionmentioning
confidence: 47%
“…The MDFT index detected in this study, 1.33, was comparable with a study conducted in North Showa, Ethiopia among school children (1.28±1.21) [ 18 ] and a study from Gondar Ethiopia (1.095±0.24) [ 15 ]. A systematic review and meta-analysis conducted by Teshome et al [ 16 ] reported a comparable mean of DMFT (1.9441). However, Teshome et al [ 16 ] reported a high mean of DMFT from Sudan (3.146) and Uganda (2.876).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has negative impacts on oral health and quality of life [2] and is one of the main reasons for the extraction of permanent teeth in Japan [3]. Dental caries is a multifactorial disease involving interactions between the diet, the host, and the microorganisms over time [4], as well as other risk factors [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%